Optimal Medical Therapy for Heart Failure and Integrated Care in Patients With Atrial Fibrillation: A Report From the ESC‐EHRA EORP Atrial Fibrillation Long‐Term General Registry - Niccolò Bonini; Marco Proietti; Giulio Francesco Romiti; Marco Vitolo; Ameenathul Mazaya Fawzy; Wern Yew Ding; Jacopo Francesco Imberti; Laurent Fauchier; Francisco Marin; Michael Nabauer; Gheorghe Andrei Dan; Tatjana S. Potpara; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Heart failure (HF) often occurs in patients with atrial fibrillation (AF), with a major impact on prognosis. Few data are available on the effect of integrated treatment strategies to improve prognosis in patients with AF. We aimed to evaluate the association between HF (according to left ventricular ejection fraction [LVEF]), HF optimal medical therapy and adherence to the Atrial Fibrillation Better Care pathway, and major outcomes in patients with AF. Methods and Results From the ESC‐EHRA EORP‐AF (European Society of Cardiology–European Heart Rhythm Association EURObservational Research Programme in Atrial Fibrillation) General Long‐Term Registry, we evaluated patients with HF, categorized according to LVEF (HF with reduced ejection fraction, HF with mildly reduced ejection fraction, HF with preserved ejection fraction). Optimal medical therapy for HF was guidelines‐defined. The primary end point was the composite of all‐cause death and major adverse cardiovascular events. From the original cohort, 9373 (84.5%) patients were included in this analysis (median age, 71 [interquartile range, 62–77] years; 39.9% women). Compared with no HF, all HF categories were associated with an increased risk of the primary composite outcome, with highest figures observed for HF with reduced ejection fraction (hazard ratio [HR], 2.36 [95% CI, 2.00–2.78]). The risk was reduced in patients with AF and HF adherent to optimal medical therapy (HR, 0.83 [95% CI, 0.70–0.98]), as well as in those adherents to the Atrial Fibrillation Better Care pathway (HR, 0.65 [95% CI, 0.48–0.88]). The effect of Atrial Fibrillation Better Care pathway was consistent across the spectrum of LVEF. Conclusions Patients with AF and HF have a high risk of major adverse events, and this risk is inversely associated with LVEF. Atrial Fibrillation Better Care pathway adherent management is associated with improved clinical outcomes in patients with HF, across the spectrum of LVEF.